Prompt Engineering Competency Enhances Employee Productivity through Human AI Collaboration in Modern Organizations - Muhlisah Lubis; Darwin Nasution (PT Agung Media Publisher, 2026)
This study aims to explore how Prompt Engineering Competency enhances employee productivity through Human–AI Collaboration in modern organizations. Employing a qualitative multiple case study approach, data were collected from 24 participants representing managers, HR professionals, educators, researchers, administrative staff, and information technology specialists who routinely utilized Generative AI in their daily work. Data were obtained through semi-structured interviews, workplace observations, and organizational document analysis and were analyzed using thematic analysis. The findings reveal three major themes. First, Prompt Engineering Competency emerged as a multidimensional strategic capability consisting of contextual prompt formulation, iterative prompt refinement, critical evaluation of AI-generated outputs, and ethical AI utilization. Second, Human–AI Collaboration significantly enhanced employee productivity through complementary intelligence, where AI accelerated routine cognitive processes while employees contributed contextual understanding, creativity, ethical judgment, and strategic decision-making. Third, organizational support including AI training, peer-learning communities, leadership commitment, and AI governance policies strengthened Prompt Engineering Competency and promoted sustainable Human–AI Collaboration across organizations. The study contributes to HRM literature by conceptualizing Prompt Engineering Competency as a distinct strategic capability that extends beyond digital competence and AI literacy. The findings provide guidance for organizations in designing competency development strategies that strengthen workforce readiness and sustainable competitive advantage in the era of Generative AI.